2016
DOI: 10.18632/oncotarget.13367
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the mitochondria-mediated apoptosis in human esophageal cancer cells by DS2, a newly synthetic diterpenoid analog, is regulated by Bax and caused by generation of reactive oxygen species

Abstract: Ent-kaurane diterpene compounds have attracted considerable attention in recent years due to its antitumor, antibacterial, and antiviral activities. However, the clinical development of natural kaurane diterpenes, for example, oridonin for cancer therapy has been hampered by its relatively moderate potency, limited bioavailability. Herein, we report a newly synthetic analog of natural ent-kaurane diterpene, DS2, which exhibits significantly improved activity of antiproliferation against various cancer cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…We found that amifostine could reduce ROS and increase SOD2 expression in TBHP-treated H9c2 cells. Mitochondria has been identified as a major source of ROS, and accumulation of ROS will cause abnormal ΔΨ m [31]. We found that amifostine was effective in preventing a decrease in ΔΨ m in TBHP-induced H9c2 cells.…”
Section: Discussionmentioning
confidence: 73%
“…We found that amifostine could reduce ROS and increase SOD2 expression in TBHP-treated H9c2 cells. Mitochondria has been identified as a major source of ROS, and accumulation of ROS will cause abnormal ΔΨ m [31]. We found that amifostine was effective in preventing a decrease in ΔΨ m in TBHP-induced H9c2 cells.…”
Section: Discussionmentioning
confidence: 73%
“…ROS are mainly produced by mitochondria and act as second messengers to control various cellular processes such as apoptosis and cell proliferation [ 35 ]. The overproduction of intracellular ROS generally causes mitochondrial dysfunction and leads to cellular oxidative stress-induced apoptosis [ 36 , 37 ]. Our study investigated the role of ROS production and the induction of apoptosis in quinalizarin-treated SW480 cells, showing that the generation of ROS influenced quinalizarin-induced cell apoptosis, MAPK, and STAT3 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Then, centrifuged the sediment in 200 μL mitochondrial extract (add DTT and protease inhibitors), and rapidly blended the mitochondrial proteins. The p53, Bax and caspase-9/-3 proteins were detected by immunoblot [7].…”
Section: Methodsmentioning
confidence: 99%